A narrativa histórica na poesia de Maria Lúcia Alvim: Romanceiro de Dona Beja - Juliana Veloso Mendes de Freitas (2015)
The present research intends to bring to light the poetry of Maria Lúcia Alvim through literary studies, especially her book 'Romanceiro de Dona Beja'. For that, we discuss the relationship between history and literature, and we propose an analysis of romanceiro as a gender and, more specifically, of 'Romancero Gitano', of Federico García Lorca, and 'Romanceiro da Inconfidência', of Cecília Meireles. The path here allows us to better understand Alvim's lyrical work and her importance as a poet. Also, from our reflections we can think about Brazilian poetry in general.